Drug checking: a potential solution to the opioid overdose epidemic? - Geoff Bardwell; Thomas Kerr (BMC, 2018)
Abstract Background North America is experiencing an overdose epidemic driven in part by the proliferation of illicitly-manufactured fentanyl and related analogues. In response, communities are scaling up novel overdose prevention interventions. Included are drug checking technologies. Main body Drug checking technologies aim to identify the contents of illicit drugs. These technologies vary considerably in terms of cost, accuracy, and usability, and while efforts are now underway to implement drug checking programs for people who inject drugs, there remains a lack of rigorous evaluation of their impacts. Conclusion Given the ongoing overdose crisis and the urgent need for effective responses, research on drug checking should be prioritized. However, while such research should be supported, it should be completed before these technologies are widely implemented.